Qualitative Study on the Influencing Factors and Countermeasures Against Job Burnout Among Organ Donation Coordinators - Luo, Ai-jing; Xu, Ze-hua; Cai, Ping-ping; He, Hai-yan; Mao, Ping; Xie, Wen-zhao (Frontiers in Public Health, 2020)
Background: Most organ donation coordinators suffer varying degrees of anxiety, depression and poor sleep caused by constant work pressure, and their professional identity is only at a medium level. All of this leads to a great risk of job burnout. Objective: To identify the influencing factors of and effective countermeasures against job burnout among organ donation coordinators. Method: Semistructured interviews were used for data collection. In-person or phone interviews were conducted from December 2017 to June 2018. Results: 12 organ donation coordinators who came from 7 different provinces and cities in China were interviewed. The interview data were sorted, and relevant topics were extracted and summarized in terms of two aspects, namely, factors that influenced job burnout in organ donation coordinators and effective countermeasures for dealing with job burnout. Conclusion: Factors influencing job burnout among organ donation coordinators include personal factors, job responsibilities, salary and benefit factors and donor family factors. Measures to help organ donation coordinators effectively address burnout include self-regulation, social support and positive events.